Effect of Core Temperature on the Oxidation of Lipids and Proteins During Steam Cooking of Large-Mouth Bass (Micropterus salmoides) - Keyu Wang; Yulong Bao; Hongxu Yang; Yong Wang; Dongpo Chen; Joe M. Regenstein; Peng Zhou (Polish Journal of Food and Nutrition Sciences)
Steam cooking is a popular way of preparing fish and the end temperature plays a key role in the quality of the cooked fish. In this study, the lipid and protein oxidation, and the related changes in volatile compounds and in vitro digestibility of large-mouth bass ( Micropterus salmoides ) steam cooked to a core temperature of 45℃, 55℃, 65℃, 75℃, and 85℃ were investigated. Steaming caused a significant increase in the peroxide value (PV) and the thiobarbituric acid-reactive substances (TBARS) value, accompanied by the decreased proportion of unsaturated fatty acids like oleic acid and linoleic acid, which was related to the lipid oxidation and the increase in volatile aldehydes as indicated by the partial least squares analysis. The protein oxidation can be reflected by the significant decrease of total thiol groups, combined with the aggregation as shown in SDS-PAGE and the increase in particle size at pre-digestive phase. And the aggregation of proteins further caused the decreased digestibility of fish meat at the gastric phase, especially when the core temperature was above 75℃. Furthermore, steaming significantly decreased the aerobic count, and no coliform or generic E. coli was detected in steamed samples. Thus the core temperature of 65-75℃ was recommended for the consideration of food oxidation and microbial safety.